2019
DOI: 10.1007/s10096-019-03613-z
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of nasal and rectal carriage of Staphylococcus aureus in intensive care unit patients

Abstract: The aim of this study was to investigate the relationship between nasal and rectal Staphylococcus aureus carriage in intensive care unit (ICU) patients and the occurrence of ICU-acquired infections related to S. aureus carriage. Three hundred and ninety-five patients admitted in ICU were screened for S. aureus nasal and rectal carriages and followed to record S. aureus infections during their stay. S. aureus strains were genotyped by arbitrarily primed PCR, spatyping, microarray and whole genome sequencing. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…Interestingly there is a report that PVL+ strains are easier to remove from carriage sites than PVL-strains [45]. Studies similar to ours, although smaller in scale and with mainly lower resolution genotyping, showed more frequent concordance between carriage strains and infection strains than we observed [46,47]. There have been implementations of S. aureus decolonisation in haemodialysis clients.…”
Section: Discussionsupporting
confidence: 62%
“…Interestingly there is a report that PVL+ strains are easier to remove from carriage sites than PVL-strains [45]. Studies similar to ours, although smaller in scale and with mainly lower resolution genotyping, showed more frequent concordance between carriage strains and infection strains than we observed [46,47]. There have been implementations of S. aureus decolonisation in haemodialysis clients.…”
Section: Discussionsupporting
confidence: 62%
“… 2006 ; Bhalla, Aron and Donskey 2007 ; van Belkum 2016 ; Gagnaire et al . 2017 , 2019 ). For instance, it was shown that diarrheal stools of patients colonized with MRSA have an important impact on the environmental contamination with these multiple drug-resistant variants, and it has even been evidenced that the intestinal tract could provide a potential reservoir for the much feared emergence of vancomycin-resistant S. aureus (Claassen-Weitz et al .…”
Section: The Human Gutmentioning
confidence: 99%
“…Importantly, this study documented endogenous infection in patients with both rectal and nasal carriage, or with rectal S. aureus carriage only (Gagnaire et al . 2019 ).…”
Section: The Human Gutmentioning
confidence: 99%
“…The link between nasal colonization with S. aureus and endogenous infection risk is well documented (Wertheim et al, 2005;Sakr et al, 2018;Gagnaire et al, 2019). Researchers have also reported the recovery of identical S. aureus isolates from the nares and ulcers of 65% of 276 patients with DFUIs based on DNA microarray profiling and concluded that nasal S. aureus colonization may be a significant DFUI risk factor (Dunyach-Remy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%